Moth - Sallis, James 1944- (Carroll & Graf, 1993)
After the murder of a close friend, Lew Griffin returns to the streets of the rural South to search for the runaway daughter he didn't know his friend had.
Keywords: African American police -- Fiction; Griffin, Lew (Fictitious character) -- Fiction; Police -- Louisiana -- New Orleans -- Fiction; Runaway children -- Fiction; New Orleans (La.) -- Fiction; Southern States -- Fiction; Mystery fiction